Hapakat Basara di Kabupaten Kapuas - Cahyo Muliawan; Muhammad Fauzan Ahsan Hafizi (AL-IBNOR, 2024)
Local wisdom has a very important role, not only in education but also in maintaining national unity. One of the Dayak local wisdoms is Hapakat Basara which means consensus in deliberation in deciding something based on customary law. The main principle of Hapakat Basara is maintaining peace. The purpose of this research is to find out whether there is until now Hapakat Basara in Kab. Kapuas, and what was done in the balai basara in Kab. Kapuas.